2014
DOI: 10.1071/ch13483
|View full text |Cite
|
Sign up to set email alerts
|

Oxyhalogen–Sulfur Chemistry: Kinetics and Mechanism of Oxidation of N-Acetyl-ʟ-methionine by Aqueous Iodine and Acidified Iodate

Abstract: The use of N-acetyl-l-methionine (NAM) as a bio-available source for methionine supplementation as well as its ability to reduce the toxicity of acetaminophen poisoning has been reported. Its interaction with the complex physiological matrix, however, has not been thoroughly investigated. This manuscript reports on the kinetics and mechanism of oxidation of NAM by acidic iodate and aqueous iodine. Oxidation of NAM proceeds by a two electron transfer process resulting in formation of a sole product: N-acetyl-l-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Our research in the past has focused on investigating the mechanism of S-oxidation of organosulfur compounds. 9,10 Extensive studies from our laboratory have shown that nearly every organic sulfur compound presents a unique reactivity and no generic oxidation pathway can be easily derived. Sulfur atom has been implicated as a site of bioactivation, resulting in formation of reactive and potentially toxic metabolites from bioactivation of sulfur containing drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Our research in the past has focused on investigating the mechanism of S-oxidation of organosulfur compounds. 9,10 Extensive studies from our laboratory have shown that nearly every organic sulfur compound presents a unique reactivity and no generic oxidation pathway can be easily derived. Sulfur atom has been implicated as a site of bioactivation, resulting in formation of reactive and potentially toxic metabolites from bioactivation of sulfur containing drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we identify a series of eight publications on iodate (IO 3 – ) reactions in aqueous solution having multistep mechanisms with a subset of three iodine-based reactions that violates the principle of detailed balancing. These publications describe oxidations by iodate of N -acetyl- l -methionine, N -acetylhomocysteine thiolactone (NAHT), methionine, cysteamine, N , N ′-dimethyl­amino­imino­methane­sulfinic acid, amidinothiourea, 2-aminoethanethiol sulfuric acid, and aminoiminomethanesulfinic acid (AIMSA) . Here, a mechanistic alternative is proposed that complies with detailed balancing.…”
mentioning
confidence: 99%
“…Four of the eight publications cited above all use the same set of rate constants for reactions , , and : k 1 = 2.8 M –3 s –1 , k –1 = 1.44 × 10 3 M –1 s –1 , k 2 = 2.1 × 10 8 M –2 s –1 , k –2 = 90 M –1 s –1 , k 3 = 8.6 × 10 2 M –2 s –1 , and k –3 = 2.00 M –1 s –1 . Thus, we obtain k 1 / k –1 = 1.9 × 10 –3 M –2 and ( k 2 / k –2 )­( k 3 / k –3 ) = 1.0 × 10 9 M –2 .…”
mentioning
confidence: 99%